KOORDINASI ANTAR UNIT DALAM PENGELOLAAN IJAZAH DI LINGKUNGAN UNIVERSITAS RIAU - Nursirwan, Nursirwan; R.F.S, Harapan Tua; Othman, Lie (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
A diploma is a document acknowledging academic achievement and/or completion of a higher education level after passing an exam held by a university. In practice, there are still many obstacles encountered in managing diplomas at the University of Riau. Starting from the slow fulfillment of requirements and documents for issuing certificates by students who are complacent in the program/faculty after the final exam, this will impact the slow preparation of files and documents carried out by the program/faculty to be sent to the rectorate. This study aims to find out the coordination of the Academic Bureau with related units in managing the issuance of diplomas and the obstacles faced by the Academic Bureau in managing the issuance of diplomas using a descriptive qualitative research method with observational data collection techniques, interviews with informants who are the Heads of the Academic and Student Affairs Bureau. Academic and Cooperation Coordinator. Rector's Academic Evaluation Sub Coordinator. PDDikti management and documentation. The results of this study indicate that with mutually agreed policies and plans as well as Standard Operating Procedures (SOP) and regulations that bind all stakeholders involved in the management of diplomas from faculties to universities, the diploma management process will run well and smoothly.